Analysis of basic nursery practice in the production of seedlings of natives species - Escobar Rodriguez, René (Bosque (Valdivia), 1990)
To accomplish reforestation programs an increasing demand for native species seedling is expected in the near future. This will require a better understanding of nursery cultivation practices to improve seedling quality. A number of important cultivation practices and the way in wich they affect indicators of seedling quality is reviewed. A list of potential harmful agents to seedling production is presented. To accomplish reforestation programs an increasing demand for native species seedling is expected in the near future. This will require a better understanding of nursery cultivation practices to improve seedling quality. A number of important cultivation practices and the way in wich they affect indicators of seedling quality is reviewed. A list of potential harmful agents to seedling production is presented.